Association of MTHFR Polymorphisms with H-Type Hypertension: A Systemic Review and Network Meta-Analysis of Diagnostic Test Accuracy. (22nd March 2022) - Kong, Yixuan; Zheng, Jinghui; Li, Lijuan; Lu, Liying; Wang, Jie
Abstract : Purpose . An association between MTHFR polymorphisms and H-type hypertension (H-HTN) has been investigated by epidemiological studies, but results have been inconsistent. Thus, a systematic assessment of the association was performed based on a literature review and pooled analysis, to provide stronger evidence on the effects of single nucleotide polymorphisms on H-HTN risk. Methods . Three investigators independently retrieved relevant studies in PubMed, Embase, Cochrane Library, China National Knowledge Infrastructure (CNKI), China Science and Technology Journal Database (VIP), Wanfang Database, and China Biomedical Literature Database (CBM). A fixed or random effects model was selected to calculate pooled odds ratio (OR) and 95% confidence intervals (CIs). A network meta-analysis of diagnostic test and Thakkinstian's algorithm were used to select the most appropriate genetic model, along with false-positive report probability (FPRP) for noteworthy associations. All data were processed using Stata 15.0 and Meta-Disc. Results . A total of 14 studies involving 1759 cases and 1581 controls for MTHFR were included in our meta-analysis. In a direct meta-analysis, we found that MTHFR C667T rs1801133 significantly increased the risk of H-HTN susceptibility except for an overdominant model. However, MTHFR A1298C rs1801131 polymorphism had no significant correlation with H-HTN risk. Besides, MTHFR C667T rs1801133 is a potential diagnostic biomarker for estimating H-HTN risk. The results indicated that the dominant model was an optimal diagnosis model for excluding diseases, which could reduce a missed diagnosis rate and further improve the accuracy of disease diagnosis. Conclusion . The present result suggests that MTHFR C667T rs1801133 polymorphism is associated with H-HTN risk and may act as a promising predictive biomarker for H-HTN risk. However, further well-designed studies are warranted to confirm these results.